LA GESTIÓN DEL CONOCIMIENTO COMO DISCIPLINA EMPRESARIAL - Puell Palacios, Juan (2008)
Knowledge Management is a new organizational paradigm that companies, today, have to consider not just to be more competitive in local markets or international, but to survive creating new products and services. Knowledge is a mental construct that falls on the abstract and, therefore, can not manage, what they really are managed are knowledge assets. There are several kinds of knowledge such as the tacit knowledge, implicit and explicit knowledge, the question is which of these skills are going to manage? We believe that knowledge must be managed to have a level of accuracy, that have the possibility of practical application and those who are new, because they do not exist anywhere else, become something that can constitute an invention or discovery that contributes to satisfy a need or desire, to improve the quality of life of human beings, or to enrich a field theoretical scientist at the same time is knowledge that can be converted into a product or service. Knowledge is typical of the people, not organizations that are not legal Entelequia think. The implicit knowledge is personal but can also be collective or group; when you have this feature is participatory, further, is the product of a discussion or debate, and this product is the one that has to be disseminated in organizations to achieve their acceptance and understanding. Product innovation is also a new knowledge. The products or services do not always have the same characteristics or virtues, as they may change in form or substance, but on condition that the user or customer feels pleasure and satisfaction with this change. We must have love for knowledge because it is not just possess it, but hope to learn more, remember that knowledge adjacent to the profound wisdom. The knowledge used to better understand, to understand and interpret what surrounds us externally and also what fills us internally. It allows us to analyze the business environment with all its factors and the inner world of the organization. Knowledge management comprises objects of analysis difficult as the person, his mind, his desire for social participation. The talented staff is the ability of a particular individual to achieve results in a company making a commitment and action in certain circumstances. Organizations must develop ongoing training and development of employees, these programs are implemented but you can not get to know the excellence of a large body of knowledge, even if it is between us. Receive new knowledge is inspiring, motivational and indispensable for a businessman.